Significance of Intermediate Values of Fractional Flow Reserve in Patients With Coronary Artery Disease. Issue 5 (2nd February 2016) - Adjedj, Julien; De Bruyne, Bernard; Floré, Vincent; Di Gioia, Giuseppe; Ferrara, Angela; Pellicano, Mariano; Toth, Gabor G.; Bartunek, Jozef; Vanderheyden, Marc; Heyndrickx, Guy R.; Wijns, William; Barbato, Emanuele
Abstract : Background—: The fractional flow reserve (FFR) value of 0.75 has been validated against ischemic testing, whereas the FFR value of 0.80 has been widely accepted to guide clinical decision making. However, revascularization when FFR is 0.76 to 0.80, within the so-called gray zone, is still debatable. Methods and Results—: From February 1997 to June 2013, all patients with single-segment disease and an FFR value within the gray zone or within the 2 neighboring FFR strata (0.70–0.75 and 0.81–0.85) were included. Study end points consisted of major adverse cardiovascular events (death, myocardial infarction, and any revascularization) up to 5 years. Of 17 380 FFR measurements, 1459 patients were included. Of them, 449 patients were treated with revascularization and 1010 patients were treated with medical therapy. In the gray zone, the major adverse cardiovascular events rate was similar (37 [13.9%] versus 21 [11.2%], respectively; P =0.3) between medical therapy and revascularization, whereas a strong trend toward a higher rate of death or myocardial infarction (25 [9.4] versus 9 [4.8], P =0.06) and overall death (20 [7.5] versus 6 [3.2], P =0.059) was observed in the medical therapy group. Among medical therapy patients, a significant step-up increase in major adverse cardiovascular events rate was observed across the 3 FFR strata, especially with proximal lesion location. In revascularization patients, the major adverse cardiovascular events rate was not different across the 3 FFR strata. Conclusions—: FFR in and around the gray zone bears a major prognostic value, especially in proximal lesions. These data confirm that FFR⩽0.80 is valid to guide clinical decision making. Abstract : Supplemental Digital Content is available in the text.